2017
DOI: 10.1093/brain/awx269
|View full text |Cite
|
Sign up to set email alerts
|

A lesion model of envy and Schadenfreude: legal, deservingness and moral dimensions as revealed by neurodegeneration

Abstract: Moral emotions have been assessed with correlational imaging techniques and framed as monolithic domains. Hernando et al. present a novel task indexing dimensions of schadenfreude and envy: deservingness, morality, and legality. An increase in both schadenfreude and envy accompanies atrophy of social cognition networks in patients with behavioural variant FTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 146 publications
(320 reference statements)
10
82
3
Order By: Relevance
“…). Another VBM study in patients with behavioral variant frontotemporal dementia and patients with Alzheimer's disease reported envy to be associated with the anterior cingulate cortex(Santamaría-García et al, 2017) Liu, Zubieta, and Heitzeg (2012). observed sex differences in these areas that might partly explain the differences in the results of the socio-emotional cognitive test part A in our study.Interestingly, although the PVS count and volume in the basal ganglia adjusted by head size did not differ significantly between family and patient groups, the visual scores in this region were significantly higher in patients compared with first-degree relatives.A previous analysis of computational versus visual neuroradiological assessments of PVS concluded that while computational measurements are least susceptible to be influenced by the overall burden of pathology in the MRI scan, neuroradiological scores capture better the full flavor of pathological versus normal features(Gonzalez- Castro et al, 2017).…”
supporting
confidence: 49%
See 1 more Smart Citation
“…). Another VBM study in patients with behavioral variant frontotemporal dementia and patients with Alzheimer's disease reported envy to be associated with the anterior cingulate cortex(Santamaría-García et al, 2017) Liu, Zubieta, and Heitzeg (2012). observed sex differences in these areas that might partly explain the differences in the results of the socio-emotional cognitive test part A in our study.Interestingly, although the PVS count and volume in the basal ganglia adjusted by head size did not differ significantly between family and patient groups, the visual scores in this region were significantly higher in patients compared with first-degree relatives.A previous analysis of computational versus visual neuroradiological assessments of PVS concluded that while computational measurements are least susceptible to be influenced by the overall burden of pathology in the MRI scan, neuroradiological scores capture better the full flavor of pathological versus normal features(Gonzalez- Castro et al, 2017).…”
supporting
confidence: 49%
“…A voxel‐based morphometry (VBM) study identified the gray matter in the dorsolateral prefrontal cortex and superior temporal gyrus as the brain regions specifically related with dispositional (i.e., not episodic) envy (Xiang et al, ). Another VBM study in patients with behavioral variant frontotemporal dementia and patients with Alzheimer's disease reported envy to be associated with the anterior cingulate cortex (Santamaría‐García et al, ). Liu, Zubieta, and Heitzeg () observed sex differences in these areas that might partly explain the differences in the results of the socio‐emotional cognitive test part A in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the social cognitive process can also transfer to moral domains in bvFTD patients, who may show altered moral judgments, displaying more utilitarian judgments in the face of moral dilemmas [ 97 , 98 ], a pattern also observed in extreme criminal terrorists [ 99 ]. Moreover, these patients can display increased antisocial and criminal behavior [ 100 , 101 ], as well as a relatively high incidence of legal violations [ 102 ] and a heightened expression of counter-empathy emotions such as envy and gloating for others' misfortunes [ 103 ].…”
Section: Social Cognition Abnormalities In Neurodegenerative Disormentioning
confidence: 99%
“…We accounted for the global atrophy pattern via a t test between groups, corrected by TIV (SPM12). Statistical significance was set at p < .001 uncorrected, extent threshold 5 50 voxels Garcia et al, 2017;García-Cordero et al, 2016;Irish, Piguet, Hodges, & Hornberger, 2014;Melloni et al, 2015;Santamaria-Garcia et al, 2017;Sedeno et al, 2014Sedeno et al, , 2016.…”
Section: Neurocognitive Status Analysismentioning
confidence: 99%